A construção de práticas pedagógicas inovadoras para a educação integral: um olhar para os processos de aprendizagem - Simas, Danielle Maria Vieira França (Universidade do Vale do Rio dos Sinos, 2022)
The present work had as main objective to analyze a set of pedagogical practices developed in Elementary School I of a school of the Jesuit Education Network, establishing possible understandings between the school's propositions and the way in which its effectiveness contributes to the learning of the students involved, considering cognitive aspects and elements related to the notions of innovation and integral education. This proposal included the analysis of guiding documents that make up the Basic Education curriculum and the methodological guidelines of Colégio dos Jesuítas, the school analyzed, in order to contribute to the clarification and implementation of processes capable of providing meaningful learning from practices innovative pedagogies. Looking at integral education as an essential horizon of the mission of the schools of the Jesuit Education Network, the research aims to provide teachers with constant reflection on their own practice, considering the teaching and learning process of students.
Keywords: Gestão da Educação Básica; Práticas pedagógicas; Educação integral; Basic Education management; Pedagogical practices; Comprehensive education; ACCNPQ::Ciências Humanas::Educação